2012
DOI: 10.1007/s10616-012-9476-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprotective activity of the isoflavones, genistein and daidzein on mutagenicity induced by direct and indirect mutagens in cultured HTC cells

Abstract: Isoflavones are phenolic compounds widely distributed in plants and found in a high percentage in soybeans. They have important biological properties and are regarded as potential chemopreventive agents. The aim of this study was to verify the preventive effect of two soy isoflavones (genistein and daidzein) by a micronucleus assay, analysis of GST activity, and real-time RT-PCR analysis of GSTa2 gene expression. Mutagens of direct (doxorubicin) and indirect (2-aminoanthracene) DNA damage were used. Hepatoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Betacyanins are derivatives of betanidin, the conjugate of betalamic acid with cyclo-Dopa. Betacyanins, including amaranthin (183), betanin (184) and isobetanin (185), were confirmed in red and black quinoa seeds, instead of anthocyanins [35]. Betaxanthins are conjugates of betalamic acid with amino acids.…”
Section: Nitrogen-containing Metabolites and Their Biological Activitmentioning
confidence: 99%
“…Betacyanins are derivatives of betanidin, the conjugate of betalamic acid with cyclo-Dopa. Betacyanins, including amaranthin (183), betanin (184) and isobetanin (185), were confirmed in red and black quinoa seeds, instead of anthocyanins [35]. Betaxanthins are conjugates of betalamic acid with amino acids.…”
Section: Nitrogen-containing Metabolites and Their Biological Activitmentioning
confidence: 99%
“…Therefore, these metabolites may help slugs in the intertidal zone with a high level of oxidative stress induced by desiccation during low tides 30 , 31 . Indeed, genistein showed antimutagenic effects with DNA damage agents at a concentration of 10 μM 32 . A similar bioactive flavonoid, apigenin, was also isolated from the intertidal aplysiid heterobranch Syphonota geographica (A. Adams and Reeve, 1850) (Aplysiidae, Tectipleura) and its food, the seagrass Halophila stipulacea (Forsskål) Ascherson, 1867 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of Gen in the diet has been linked to decreased rates of metastatic cancer in a number of population-based studies [ 33 ]. In HCC, Gen has anti-mutagenic activity [ 34 ] and induces apoptosis [ 35 ]. In the present study, we showed for the first time that Gen suppresses TPA-induced cell invasive activity and MMP-9 expression by reducing tumor migration and invasion of HCC.…”
Section: Discussionmentioning
confidence: 99%